CONSUMER PROFILE OF KNOWLEDGE IN RURAL - EDUCATION AND AGE - Tudorica, Andra-Valentina; Mirescu, Livia (Economics of Agriculture, 2012)
Education and therefore learning is the main pillars that form the new generation of society, the student is the focus of the work carried on and the performance gained during years of study. Problems currently affecting the whole rural educational system by very low possibilities to advance professionally, being found among the determining factors: standard of living low and insufficient funds allocated for education. In terms of age, the evolution of Romanian rural area is marked by a real decline, manifested in the aging population, low birth and fertiliate, external migration and depopulation of certain areas strong.